Fulvic Acid Alleviates Paper Sludge Toxicity in Canola (Brassica napus L.) by Reducing Cr, Cd, and Pb Uptake - Khilji, Sheza Ayaz; Sajid, Zahoor Ahmad; Fayyaz, Sidra; Shah, Anis Ali; Shah, Adnan Noor; Rauf, Mamoona; Arif, Muhammad; Yang, Seung Hwan; Fiaz, Sajid (Frontiers in Plant Science, 2022)
Heavy metal toxicity reduces growth and development of crop plants growing in metal contaminated regimes. Disposal of industrial waste in agricultural areas exert negative effects on physiochemical activities of plants. This research aimed to examine the fulvic acid (FA) mediated efficacy of Brassica napus L. regarding stress tolerance in soil amended with paper sludge (PS). For this purpose, plants were grown for 90 days under greenhouse conditions at various concentrations of PS amended soils (0%, 5%, 10%, and 15%) being irrigated with water containing FA (0%, 10%, and 20%). All the physicochemical parameters of PS were carried out before and after plant transplantation. Paper sludge toxicity reduced growth (shoot/root length, fresh/dry weight of shoot/root, No. of flower and leaves) and physicochemical characteristics of exposed B. napus plants. In comparison, FA application improved growth by reducing the metal uptake in the shoot of plants grown at various concentrations of PS. An increasing trend in antioxidant enzymes activities was observed by increasing concentration (0-10 and 20%) of FA. Post-harvest analysis indicates that the amount of tested metals was significantly reduced at all PS concentrations of. Minimum metal uptake was observed at 0% and maximum at 15% concentration of paper sludge. Additionally, FA application at 20% concentration reduced Chromium (Cr), Cadmium (Cd) and Lead (Pb) uptake in the shoot from 6.08, 34.42 and 20.6 mgkg-1 to 3.62, 17.33 and 15.22 mgkg-1, respectively. At this concentration of paper sludge in the root, 20% FA reduced Cr, Cd and Pb uptake from 11.19, 44.11 and 35.5 mgkg-1 to 7.88, 27.01 and 24.02 mgkg-1, respectively. Thus, FA at 20% concentration is suggested as an effective stimulant to mitigate the metal stress in B. napus grown in paper sludge polluted soil by reducing metal uptake and translocation to various plant parts.